Genetic Analysis for Cooking and Eating Quality of Super Rice and Fine Mapping of a Novel Locus qGC10 for Gel Consistency - Zhang, Anpeng; Gao, Yang; Li, Yuanyuan; Ruan, Banpu; Yang, Shenglong; Liu, Chaolei; Zhang, Bin; Jiang, Hongzhen; Fang, Guonan; Ding, Shilin; Jahan, Noushin; Xie, Lihong; et al. (Frontiers in Plant Science, 2020)
Rice (Oryza sativa L.) is an important cereal that provides food for more than half of the world’s population. Besides grain yield, improving grain quality is also essential to rice breeders. Amylose content (AC), gelatinization temperature (GT) and gel consistency (GC) are considered to be three indicators for cooking and eating quality in rice. Using a genetic map of RILs derived from the super rice Liang-You-Pei-Jiu with high-density SNPs, we detected 4 QTLs for AC, 3 QTLs for GT and 5 QTLs for GC on chromosomes 2, 3, 4, 5, 6, 10 and 12. Wx locus, an important determinator for AC and GC, resided in one QTL cluster for AC and GC, qAC6 and qGC6 here. And a novel major QTL qGC10 on chromosome 10 was identified in both Lingshui and Hangzhou. With the BC4F2 population derived from a CSSL harboring the segment for qGC10 from 93-11 in PA64s background, it was fine mapped between two molecular markers within 181 kb region with 27 annotated genes. Quantitative real-time PCR results showed that eight genes were differentially expressed in endosperm of two parents. After DNA sequencing, only LOC_Os10g04900, which encodes a F-box domain containing protein, has 2 bp deletion in the exon of PA64s, resulting in a premature stop codon. Therefore, LOC_Os10g04900 is considered to be the most likely candidate gene for qGC10 associated with gel consistency. Identification of qGC10 provides a new genetic resource for improvement of rice quality.